Enhancing Website Usability by Utilizing Heuristic Evaluation and User Feedback for Better User Experience - Sulthan Habib; Tengku Khairil Ahsyar; M. Afdal; Febi Nur Salisah; Syaifullah Syaifullah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
This research focuses on improving the usability of the Portal KUKERTA website used by Lembaga Penelitian dan Pengabdian pada Masyarakat Universitas Riau (LPPM UNRI) for the Kuliah Kerja Nyata (KKN) program. Based on direct observations of the Portal KUKERTA website, several usability issues related to the system were identified. Combining heuristic evaluation and user feedback, the study aims to enhance the user experience and ensure a user-friendly interface. Analysis of feedback from 98 users revealed the highest severity ratings in Flexibility and Efficiency of Use, Error Prevention, and User Control and Freedom. Recommendations were developed to address these issues and improve the user experience. The integration of heuristic evaluation and user feedback provides valuable insights for enhancing the usability of the Portal KUKERTA website, serving the needs of students and lecturers. Additionally, the research results showed scores for various usability principles, including visibility of system status (1.838), match between system and real world (2.264), user control and freedom (3.786), consistency and standards (2.325), error prevention (4.062), recognition rather than recall (2.250), flexibility and efficiency of use (4.075), aesthetic and minimalist design (2.713), and help users recognize, diagnose, and recover from errors (2.843). These findings further guide the improvement of specific areas to enhance the overall usability of the Portal KUKERTA website.